Challenges and strategies in change management in digital transformation projects: a qualitative study based on interviews - Carvalho, Muriel Lacerda; Souza, Vinicius Costa de; Simões, Wagner Lourenzi (Brazilian Journal of Production Engineering, 2026)
This study aims to analyze the main challenges and strategies associated with change management in digital transformation projects. It is a qualitative and exploratory study based on semi-structured interviews with four professionals directly involved in digital transformation initiatives. The results indicate that the main challenges are related to cultural resistance, lack of organizational readiness, and employee engagement, while the most effective strategies involve continuous communication, active leadership, and the training of those involved. The study contributes by systematizing empirical evidence on change management in digital transformation contexts, offering practical insights for managers and researchers in the field.
Keywords: Digital Transformation; Change Management; Project Management